Two-Step Analog-Digital Multiuser Equalizer for Hybrid Precoded mmWave Communications - Magueta, R.; Castanheira, D.; Silva, A.; Dinis, R.; Gameiro, A. (2018 IEEE Globecom Workshops (GC Wkshps), 2018)
In this paper we propose a hybrid multi-user multi-stream equalizer combined with low complexity analog-digital precoders for uplink broadband millimeter wave massive multiple-input-multiple-output (MIMO) systems. Although hybrid analog/digital MIMO techniques were originally proposed for flat fading channels, there is a growing interest in using these techniques in frequency-selective channels such as the ones associated to broadband wireless systems. However, it is expected the development of wideband solutions, and then it is crucial to propose transmit and receive schemes for frequency selective channels. The proposed two-step iterative analog-digital equalizer is designed by minimizing the sum of the mean square error of all subcarriers. The analog part is constant over the subcarriers and the iterations due to hardware constraints, while the digital part is iterative and computed on per subcarrier basis. The results show that the proposed multiuser equalizer achieves a performance close to recently proposed fully iterative analog-digital equalizers, while being more suited for practical applications.